Radiological protection of foetuses and breast-fed children of occupationally exposed women in nuclear medicine – Challenges for hospitals. (November 2017) - Almén, A.; Mattsson, S.
Highlights: Great variation and uncertainties regarding the occupational dose levels result in great uncertainties in foetal dose assessments. Potential exposures due to accidents have to be considered and taken into account. ICRP constraints for foetuses and breastfed children should be followed. Work with no restrictions as well as work not to be done during pregnancy and breastfeeding should be unambiguously define. Declaration of pregnancy or breastfeeding is of fundamental importance. Abstract: This paper describes issues of concern for protecting foetuses and breast-fed children of occupationally exposed women in nuclear medicine from unnecessary exposure of ionising radiation. The protection principle is to ensure the same level of protection for the foetus and child as for the general public. Therefore international radiation protection standards recommend a dose constraint of 1 mSv to a foetus during the remaining time of pregnancy after it is known/declared and a yearly dose constraint of 1 mSv to a breast-fed child. It is not self-evident how to guarantee this level of radiation protection. The exposure situation in nuclear medicine is complex. Exploring existing reported occupational exposure levels suggests great variability between work tasks and facilities. The standards and guidelines found give no detailed advice. Therefore each facility needs to systematically review external and internal exposure levels in order to plan appropriate protection measures and issue their own guidelines and rules. One strategy might be that each facility defines tasks that do not require any restrictions and lists such duties that are not suitable to do when pregnant or breastfeeding, taking also potential exposure levels into consideration. This paper gives examples of such types of work. Information to the staff about the necessity of declaring pregnancy or breastfeeding is of fundamental importance. The internal policies issued by the hospital management should make clear the basis for taking care of pregnant and breastfeeding employees.